2022
DOI: 10.1177/24730114221102456
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Early Complications Following Total Ankle Arthroplasty

Abstract: Background: The safety of outpatient total ankle arthroplasty (TAA), and factors predictive of early complications are poorly understood. The objective of this study was to determine the frequency of early complications in patients undergoing outpatient TAA compared to a matched inpatient TAA cohort. Factors predictive of early complications following TAA are elucidated. Methods: A retrospective review of prospectively collected data from the 2011-2018 American College of Surgeons–National Surgical Quality Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Prior studies have similarly found baseline differences in patients undergoing outpatient and inpatient TAA. 1 , 6 , 22 , 28 Previous studies have shown increased complication and revision rates in TAA in patients with obesity and diabetes. 10 , 25 We did not observe a difference in BMI or in diabetes prevalence at baseline between the same-day discharge TAA group and the inpatient TAA group, suggesting that these factors are not of high importance in determining patient selection for same-day discharge at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have similarly found baseline differences in patients undergoing outpatient and inpatient TAA. 1 , 6 , 22 , 28 Previous studies have shown increased complication and revision rates in TAA in patients with obesity and diabetes. 10 , 25 We did not observe a difference in BMI or in diabetes prevalence at baseline between the same-day discharge TAA group and the inpatient TAA group, suggesting that these factors are not of high importance in determining patient selection for same-day discharge at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, type 2 diabetes and smoking are known risk factors for TAA. 12,21,54 However, the role of excess weight or obesity as a prognostic factor for TAA is still under debate. 20,31,33,37…”
Section: Introductionmentioning
confidence: 99%
“…For example, type 2 diabetes and smoking are known risk factors for TAA. 12,21,54 However, the role of excess weight or obesity as a prognostic factor for TAA is still under debate. 20,31,33,37 In orthopaedic clinical practice, body weight is a crucial criterion in patient selection since the negative effect of higher body mass index (BMI) on hip and knee arthroplasty outcomes is proven.…”
Section: Introductionmentioning
confidence: 99%